COVID-19 Vaccines Coverage in Afghanistan: a descriptive analysis of secondary data from DHIS2 - Hamidullah Matin; Khwaja Mir Islam Saeed; Mir Salamuddin Hakim; Shoaib Naeemi (Razi International Medical Journal, 2023)
Background: Mass immunization is an economical and effective way to control the pandemic of COVID-19. Afghanistan started its first COVID-19 vaccination campaign at the national level in February 2021. Upon initiation, 10 target groups have been given priority to get vaccinated. This study focuses on a descriptive analysis of COVID-19 vaccination coverage at the national level.